Different Post-Sowing Nitrogen Management Approaches Required to Improve Nitrogen and Water Use Efficiency of Canola and Mustard - Riar, Amritbir; Gill, Gurjeet; McDonald, Glenn (Frontiers in Plant Science, 2020)
Strategic use of nitrogen (N) may improve N use efficiency, but there is limited information on the influence of N supply at crucial growth stages on N accumulation, water use and water use efficiency of canola and mustard. In this study, we hypothesize that genetic variation among canola and mustard can alter the response of timing and rate of post-sowing N application at targeted phenological growth stages by improving N and water use and their efficiencies. Field experiments were conducted in South Australia during two growing seasons with contrasting water availabilities. Two mustard and four canola cultivars, including two triazine tolerant (TT) and two non-TT cultivars were evaluated under different post-sowing N application strategies comprising three N rates and different timings of application. Mustard used more water than canola in the season with higher rainfall, but canola and mustard used similar amounts of water in the drier season. Nitrogen increased the water use efficiency (WUE) of canola and mustard cultivars. Nitrogen rate and timing did not influence the total water use of canola and mustard but influenced the partitioning of pre- and post-flowering water use. Even though, highest N uptake was observed in the treatment with continuous supply of N with 200 kg N ha-1 in five splits it did not influence the N efficiencies parameters which indicate that yield of canola and mustard are limited by N rate in these environments. In treatment with limited N supply, targeting N at the rosette stage improve N use efficiency of canola and mustard. However, the limited N uptake potential of mustard makes timing of N application the most important consideration whereas correct N rate should be main consideration for canola.